Variations of Sagittal Alignment in Standing Versus Sitting Positions Under the Roussouly Classification in Asymptomatic Subjects. Issue 5 (June 2022) - Sun, Zhuoran; Zhou, Siyu; Jiang, Shuai; Zou, Da; Yu, Miao; Li, Weishi
Study Design: Prospective radiological analysis. Objective: To investigate the characteristics of the sagittal spinopelvic alignment in the standing and sitting positions under the Roussouly classification in a healthy population. Methods: This study using standing and sitting lateral radiographs included 143 volunteers whose spinopelvic parameters were measured. The parameters were compared in the standing and sitting positions. The lumbo-pelvic profile was identified according to the Roussouly classification. The differences in the values of the parameters between the standing and sitting positions were analyzed. The different frequencies of the unchanged apex were assessed. Results: All parameter values except the thoracolumbar angle (TLK) were significantly altered. With regard to the classification of the lumbopelvic profile, 15 (10.5%) subjects were excluded because they were evaluated as not belonging to any of the Roussouly types. The remaining 128 subjects were evaluated and classified as follows: 19 (14.8%), type 1; 53 (41.4%), type 2; 9 (7.0%), type 3 + anteverted pelvis (AP); 33 (25.8%), type 3; and 14 (10.9%), type 4. The differences in the pelvic tilt (PT), sacral slope (SS), and thoracic pelvic angle (TPA) values were significantly lower in types 1 and 2 than in other Roussouly types. Corresponding variations in the apical vertebra for the sagittal lumbar curves in the sitting position were observed. Conclusions: Subjects with Roussouly type 1 and type 2 sagittal alignments were found to be less capable of performing changes in alignment when changing to the sitting position. The characteristics of the apical movement were also different.